Handstitched in space and time: the story of a vintage patchwork cloak. Issue 17 (9th December 2022) - Pugh, Esther
Abstract : This article explores the spatial and temporal qualities of a vintage hand-sewn patchwork cloak, discovered by the author on eBay. Using Shim's three-stage consumption process of 'acquisition, possession and disposal' of things (1995), the cloak is followed on a journey through multiple transitions, paths and diversions, including 'connoisseurship', 'keeping' and 'passing on' to others. At each consumption stage, (acquisition, possession and disposal), the spatial and temporal aspects of the cloak's biography are investigated, such as the online sites, the shops and the domestic spaces it occupies, the time taken to find such original pieces, and the time they last through multiple circular lifecycle iterations. The practices of second-hand and craft consumption are found to be complex, involving multiple sites, and travelling through the past, present and future of the imagination and of actual spaces. It is found that self-identity, relationships and knowledge are fundamental to every life stage of the biography of this cloak as it transitions through multiple lives.